A new insight from space into swell propagation and crossing in the global oceans - Xiao‐Ming Li (Geophysical Research Letters)
Abstract A half‐century ago, it was recorded that ocean swells can propagate up to halfway around the globe. However, from a global perspective, how ocean swells propagate in the global oceans has yet to be depicted. To date, synthetic aperture radar (SAR) is the only available remote sensing instrument to measure the two‐dimensional information of ocean surface waves. Here a 10 year (2002–2012) global wave data set of the spaceborne advanced SAR on board the European Space Agency's satellite Envisat and the global wind data set of the WindSat were used to (1) depict the propagation routes of ocean swells in the global oceans, (2) identify four distinguished crossing swell “pools,” and (3) interpret how these pools are formed. Together, these findings yield a new insight into ocean swells propagation and the consequent occurrence of crossing swells on a global ocean scale from space, which will further deepen our understanding of nature of ocean.